Osteoimmuno-Oncology: Therapeutic Opportunities for Targeting Immune Cells in Bone Metastasis - Tiina E. Kähkönen; Jussi M. Halleen; Jenni Bernoulli (Cells, 2021)
Immunotherapies provide a potential treatment option for currently incurable bone metastases. Bone marrow is an important secondary lymphoid organ with a unique immune contexture. Even at non-disease state immune cells and bone cells interact with each other, bone cells supporting the development of immune cells and immune cells regulating bone turnover. In cancer, tumor cells interfere with this homeostatic process starting from formation of pre-metastatic niche and later supporting growth of bone metastases. In this review, we introduce a novel concept osteoimmuno-oncology (OIO), which refers to interactions between bone, immune and tumor cells in bone metastatic microenvironment. We also discuss therapeutic opportunities of targeting immune cells in bone metastases, and associated efficacy and safety concerns.